2016
DOI: 10.1111/josh.12362
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Education Lessons and Recesses in School Lifestyle of Adolescents

Abstract: BACKGROUNDThis study investigates school lifestyle among adolescents in terms of physical activity (PA) structure: (1) adolescents participating in a physical education lesson (PEL) versus (2) aggregate recess time exceeding 60 minutes.METHODSThe research was conducted in 24 secondary schools in the Czech Republic (boys N = 208, girls N = 433). For the whole day (1-3 days) participants wore the ActiTrainer accelerometer, which monitored PA, and heart rate. A total of 1122 school days were recorded.RESULTSBoth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 41 publications
3
77
0
9
Order By: Relevance
“…e primary finding of this study is that participants who reported AS in lessons did not have lower levels of PA during recesses or after school. Given the overall low PA of adolescents during recesses [38,41], this finding highlights the major challenge of raising PA during recesses among all adolescents. Previous studies often note the presence of insufficient PA during recesses [42] and interventions aimed at increasing PA during recesses have been generally unsuccessful [43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…e primary finding of this study is that participants who reported AS in lessons did not have lower levels of PA during recesses or after school. Given the overall low PA of adolescents during recesses [38,41], this finding highlights the major challenge of raising PA during recesses among all adolescents. Previous studies often note the presence of insufficient PA during recesses [42] and interventions aimed at increasing PA during recesses have been generally unsuccessful [43].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we present results concerning moderate-to-vigorous PA (MVPA) intensity (60-100% HRmax, ≥3 METs). e accelerometer data were processed consistent with previously published methods [38][39][40][41].…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
“…Szkolne aktywne 30 minut można zrealizować w dniu z lekcją wychowania fizycznego w planie lekcji. Co natomiast w dniami, w których tej lekcji nie ma?Kolejne zalecenie to 3000 kroków podczas pobytu ucznia w szkole [14], łatwe do zrealizowania w dni z lekcją WF. Co z pozostałymi dniami szkolnymi?…”
Section: Dyskusjaunclassified
“…Poza tym szkolna aktywność fizyczna objętościowo powinna stanowić 25% sumy całego czasu spędzanego przez ucznia w szkole, a przynajmniej 50% sumy czasu wszystkich przerw międzylekcyjnych powinno być aktywne fizycznie. Podczas przerwy 10-minutowej uczeń powinien wykonywać 250 kroków, a 20-minutowej -500 kroków [14].…”
unclassified
“…On the other hand, the number of steps is a unique value and easy for interpretation. Compliance to hip-worn accelerometer or pedometer can be affected by (1) the respondent's willingness to wear a pedometer or accelerometer for a specified period (Frömel, Svozil, Chmelík, Jakubec, & Groffik, 2016); (2) willingness to put the device back on after changing clothes and to remove the device for the period of sleeping, personal hygiene and for water sport (Fairclough et al, 2015). This can be resolved by using wrist activity trackers (WATs); these are accelerometer devices which attempt to provide users with an easy way to objectively monitor their PA (J. M. Lee, Kim, & Welk, 2014).…”
Section: Introductionmentioning
confidence: 99%